The relationship between parents involvement, self esteem and academic motivation among students - Muniandy, Renuka (2021)
The purpose of this research is to study the Correlation Study of Students’ Self Esteem and Academic Motivation especially on Covid-19 Pandemic. . There is not much study was carried on Parents involvement between students self esteem and academic motivation. Although there were many studies have been conducting on students’ academic achievement, as far as I know, no research has investigated the relationship between parents support and students self esteem and learning motivation, especially during the Covid-19 pandemic taking into account on students self esteem. The research involved 331 respondents from age 13 to 16 years old. A Google form questionnaire has been used as instrument to collect the desired data for this study. It is a Likert scale questionnaire which is consisting of forty nine questions. The survey data was gathered using Parent’ involvement which is developed by Cadosles Rosid Benilde Q et al., (2017), Rosenberg Self Esteem Scale (1965), and Academic Motivation Scale (AMS) which has been adopted and adapted from Vallerland et al., (1992). The collected data was then analyzed thoroughly by means of descriptive statistics (mean and percentage) and Non Parametric analysis (Spearman Correlation). Overall the findings show that Parents Involvement are in high level while students self esteem is in low level and Academic Motivation shows high level of mean interpretation. However there are significant relationship between parents’ involvement in students self esteem and academic motivation.